1976
DOI: 10.1073/pnas.73.12.4575
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin-A-induced transmembrane linkage of concanavalin A surface receptors to intracellular myosin-containing filaments.

Abstract: With normal rat kidney cells in monolayer culture, we have studied the distribution on the cell surface of receptors for concanavalin A, and the distribution of the smooth muscle myosin-like protein inside the same cell, using specific fluorescence microscopic methods. The concanavalin A receptors were initially uniformly dispersed over the cell surface, but 20 min after the addition of concanavalin A at 370, the receptors showed a variety of nonuniform surface distributions, including extended parallel linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 20 publications
(20 reference statements)
5
35
0
Order By: Relevance
“…Initially, the fluorescence covered the cell surface uniformly with no discernible structure, in accordance with the earlier report of Ash and Singer (1976, Fig. 5 a).…”
Section: Con a Patterns In Normal And C-src Overexpresser Nih 3t3 Cellssupporting
confidence: 92%
See 3 more Smart Citations
“…Initially, the fluorescence covered the cell surface uniformly with no discernible structure, in accordance with the earlier report of Ash and Singer (1976, Fig. 5 a).…”
Section: Con a Patterns In Normal And C-src Overexpresser Nih 3t3 Cellssupporting
confidence: 92%
“…The labeling of the ConA receptors was effected following the procedure of Ash and Singer (1976). The coverslips maintained in 35-ram dishes on which cultured ceils were grown, rinsed three to four times with serum-free DME, and incubated with 1 ml of the same medium containing 50 t~g of either unlabeled ConA or F-ConA for various times at 370C.…”
Section: Fluorescence Studies and Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…In chick fibroblasts infected with Newcastle disease virus (NDV), this is indicated by both an alteration of the membrane-operated uptake of metabolic precursors and an altered response to the agglutinating effect of plant lectins (Rott et al, 1975;Reeve et al, 1975). The existence of functional associations between surface macromolecules and cytokinetic elements (Ash & Singer, 1976;Sundquist & Ehrnst, 1976;Toh & Hard, 1977;Schreiner et al, 1977;Koch & Smith, 1978;Flanagan & Koch, 1978;Thom et al, 1979;Hoesli et al, 1980) may also be of importance in the evolution of some virus infections as it has been observed that translation of vesicular stomatitis virus (VSV) requires ribosomal association with the cytoskeletal framework (Cervera et al, 1981) and that macromolecular changes at the cell exterior can affect the organization of microfilament structures (Mallucci & Wells, 1976;Wells & Mallucci, 1978). On the other hand, since cytoskeletal elements can play a role in the control and display of cell surface macromolecular components (De Petris, 1974;Nicolson, 1975;Yahara & Edelman, 1975;Sundquist & Ehrnst, 1976;Edelman, 1976), a primary alteration of the cytoskeleton may lead to structural and functional changes of the surface membrane, which may in turn alter the assembly and release of membrane-bound (enveloped) viruses and modify the cytopathic effect that they cause.…”
Section: Discussionmentioning
confidence: 99%